2021
DOI: 10.1038/s41419-020-03368-y
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress activates NORAD expression by H3K27ac and promotes oxaliplatin resistance in gastric cancer by enhancing autophagy flux via targeting the miR-433-3p

Abstract: Oxaliplatin resistance undermines its curative effects on cancer and usually leads to local recurrence. The oxidative stress induced DNA damage repair response is an important mechanism for inducing oxaliplatin resistance by activating autophagy. ELISA is used to detect target genes expression. TMT-based quantitative proteomic analysis was used to investigate the potential mechanisms involved in NORAD interactions based on GO analysis. Transwell assays and apoptosis flow cytometry were used for biological func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 37 publications
0
49
0
Order By: Relevance
“…On account of that Tanshinone IIA is able to increase the sensitivity of various drug‐resistant gastric cancer cells to first‐line chemotherapeutic drugs, 28,34 we hypothesized that Tanshinone IIA could improve chemotherapy resistance through reducing tumor stemness, which is directly related to chemo‐resistance 35 . BGC‐823 and SGC‐7901 were used as gastric adenocarcinoma models because many researches have showed that BGC‐823 cells and SGC‐7901 cells represent undifferentiated and moderately differentiated gastric cancer cells, respectively 36–39 . There have been some researches about Tanshinone IIA which plays an important role in inhibiting tumor stem cells.…”
Section: Discussionmentioning
confidence: 99%
“…On account of that Tanshinone IIA is able to increase the sensitivity of various drug‐resistant gastric cancer cells to first‐line chemotherapeutic drugs, 28,34 we hypothesized that Tanshinone IIA could improve chemotherapy resistance through reducing tumor stemness, which is directly related to chemo‐resistance 35 . BGC‐823 and SGC‐7901 were used as gastric adenocarcinoma models because many researches have showed that BGC‐823 cells and SGC‐7901 cells represent undifferentiated and moderately differentiated gastric cancer cells, respectively 36–39 . There have been some researches about Tanshinone IIA which plays an important role in inhibiting tumor stem cells.…”
Section: Discussionmentioning
confidence: 99%
“…After silencing NORAD, miR-877-3p was upregulated and CREBBP was downregulated in OS cells treated with EVs. The binding relationship between CREBBP and NORAD has been identified earlier [ 33 ]. Similarly, the current study ascertained that NORAD carried by BMSC-EVs promoted CREBBP expression by sponging miR-877-3p.…”
Section: Discussionmentioning
confidence: 95%
“…It has been reported that DNA damage triggers a decrease in cellular H3K27ac levels ( 33 ) or induces an enrichment of H3K27ac at specific promoter regions ( 34 ). Accordingly, our data showed that the levels of both H3.1K27ac and H3.3K27ac decreased after UV radiation.…”
Section: Discussionmentioning
confidence: 99%